Linking benefits to balanced scorecard strategy map - Gomes, J.; Romão, M.; Caldeira, M. (Advances in Intelligent Systems and Computing, 2013)
In this paper the authors propose a link between the Benefits Dependency Network, from a Benefits Management approach, and a Strategy Map, from Balanced Scorecard, to improve the management of business benefits and to ensure that actions taken along the investment life-cycle lead to foreseen benefits realization. The goal of this integration is to build a framework that combines useful features of both methods. We sustain that they can be complementary. As a Strategy Map is committed with strategic alignment, communication and monitoring of strategy execution at all levels of an organization, a Benefits Dependency Network is aimed at explaining how benefits are going to be obtained through organizational change. Using the results of a case-study research, we explain how a Strategy Map can cross with the Benefits Dependency Network. The integrated contribution is meant to increase the investments effectiveness, giving to stakeholders the confidence on a clearer delivery path for their expected benefits.